Pengaruh Tourist Motivation dan Tourist Attraction Terhadap Tourist Satisfaction Serta Dampaknya Pada Tourist Benefit di Masa Pandemi Covid 19 (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS DR SOETOMO SURABAYA, 2022)
The tourist village is a unique destination because in addition to having natural attractions, community life and interactions are unique and still original. This peculiarity makes tourist villages with one another have differences that cannot be imitated. Tourist villages during the COVID-19 pandemic became an alternative to safe outdoor destinations in terms of recreation and health. The objectives of this research are 1). to determine the significant effect of Tourist Motivation on Tourist Satisfaction. 2). Does Tourist Attraction have a significant effect on Tourist Satisfaction. 3). to determine the significant effect of Tourist Motivation on Tourist Benefit. 4). to determine the significant effect of Tourist Satisfaction on Tourist Benefit. This research was conducted in the Nglanggeran Tourism Village, Gunungkidul. The sample in the researcher is tourists who have visited the Nglanggeran Tourism Village. The number of tourists who became the sample as many as 128 people. Dissemination of the questionnaire in the form of a google form by sending a questionnaire link to social media such as WhatsApp Story and placing a questionnaire link in the Instagram bio and Instagram story and distributing the questionnaire link on twitter. The analysis technique uses SEM AMOS. The results showed 1). Tourist Motivation has a significant effect on Tourist Satisfaction. 2). Tourist Attraction has a significant effect on Tourist Satisfaction. 3). Tourist Motivation has a significant effect on Tourist Benefit. 4). Tourist Satisfaction has a significant effect on Tourist Benefit.)